2015
DOI: 10.1016/j.dcn.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

A DTI tractography study in pre-readers at risk for dyslexia

Abstract: In adults and school-aged children, phonological aspects of reading seem to be sustained by left dorsal regions, while ventral regions seem to be involved in orthographic word recognition. Yet, given that the brain reorganises during reading acquisition, it is unknown when and how these reading routes emerge and whether neural deficits in dyslexia predate reading onset. Using diffusion MRI in 36 pre-readers with a family risk for dyslexia (FRD(+)) and 35 well matched pre-readers without a family risk (FRD(-)),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
113
4
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 70 publications
14
113
4
3
Order By: Relevance
“…This finding was also reflected in negative MD and RD relationships of the said ventral tracts with reading scores. This early emergence of ventral tracts for reading has been supported by previous studies [50,52,53] and may reflect a compensatory strategy associated with the maturation of dorsal tracts [54]. More specifically, the dorsal tracts mature later than ventral tracts, and thus, may be insufficient for phonological processing in and of themselves [54,55].…”
Section: Ventral Tracts Reading Acquisitionsupporting
confidence: 61%
“…This finding was also reflected in negative MD and RD relationships of the said ventral tracts with reading scores. This early emergence of ventral tracts for reading has been supported by previous studies [50,52,53] and may reflect a compensatory strategy associated with the maturation of dorsal tracts [54]. More specifically, the dorsal tracts mature later than ventral tracts, and thus, may be insufficient for phonological processing in and of themselves [54,55].…”
Section: Ventral Tracts Reading Acquisitionsupporting
confidence: 61%
“…Developmentally, individual variations in diffusion properties of dorsal and ventral white matter pathways have been found to be associated with phonological skills in pre-reading children (Saygin et al 2013; Vanderauwera et al 2015; Vandermosten et al 2015) and with reading skills in older children who had learned to read (Nagy et al 2004; Beaulieu et al 2005; Deutsch et al 2005; Niogi and McCandliss 2006; Odegard et al 2009; Rimrodt et al 2010; Yeatman et al 2011; Gullick and Booth 2014; Gullick and Booth 2015). Diffusion properties have also been observed to change in association with improvements in children's reading abilities following an intensive behavioral training for reading (Keller and Just 2009) and to predict later reading outcomes in children with dsylexia (Hoeft et al 2007).…”
mentioning
confidence: 99%
“…Based on dMRI studies of reading and white matter in children, we evaluated the anterior SLF and the arcuate fasciculus, the inferior longitudinal fasciculus, the corticospinal tract, the uncinate fasciculus, and posterior subdivisions of the splenium of the corpus callosum that contain fiber pathways projecting to temporal or occipital cortices. (Nagy et al 2004; Beaulieu et al 2005; Deutsch et al 2005; Niogi and McCandliss 2006; Frye et al 2008; Qiu et al 2008; Odegard et al 2009; Yeatman et al 2011; Yeatman, Dougherty, Ben-Shachar, et al 2012; Saygin et al 2013; Vanderauwera et al 2015; Vandermosten et al 2015). In tracts where we identified group differences, we planned to conduct correlation analyses between white matter properties and specific reading-related skills in order to interrogate the possible sources of individual variability that may have contributed to the observed group differences in white matter structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study observed FA of the left arcuate fasciculus and bilateral inferior fronto-occiptial fasciculi correlates with phonological awareness in Dutch speaking pre-readers with (N=36) and without a familial risk of DD (N=35) [48]. Children completed behavioral testing at the start of kindergarten and an MRI scan at the end of the academic year.…”
Section: The Role Of the Arcuate Fasciculus In Reading And Developmenmentioning
confidence: 99%